PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM TRANSAKSI DIGITAL DENGAN MODUS PENIPUAN - Muhammad, Ridwan Maulana; Marwiyah, Siti; Aranggraeni, Renda; Paramitha, Vallencia Nandya (Gapenas Publisher, 2025)
The level of information technology development has encouraged an increase in digital trade transactions through e-commerce platforms, one of which is Shopee. This phenomenon provides convenience for consumers, but it also raises serious issues in the form of criminal fraud and illegal trade that harm society. The urgency of this research lies in the increasing number of digital fraud cases that test the effectiveness of legal regulations, particularly the Consumer Protection Law and the Electronic Information and Transaction Law. This study aims to answer questions about the forms of criminal acts in digital transactions through Shopee and how legal protection is provided to consumers based on Indonesian positive law. This study uses a normative legal research design with a qualitative approach. Data was collected through a literature study, covering primary legal materials in the form of laws and court decisions, as well as secondary legal materials from academic literature. Two Supreme Court decisions, namely Decision Number 109 K/Pid.Sus/2024 and Number 951 K/Pid.Sus/2020, were used as case studies to assess the application of law in digital consumer protection. The analysis was conducted descriptively and analytically by interpreting legal norms and relating them to the context of practice. The results of the study show that digital transactions are prone to being exploited for criminal acts of subsidised price fraud and the distribution of prohibited goods. Legal protection through the UUPK and UU ITE still faces obstacles, particularly in terms of digital evidence, low consumer legal literacy, and limited online dispute resolution mechanisms. This study contributes to expanding the study of consumer protection law by integrating the perspectives of criminal law, cyber law, and jurisprudence. The conclusion of this study emphasises the need for regulatory updates, increased digital literacy, and strengthened obligations for e-commerce platforms to protect consumers. Further research is recommended to examine the effectiveness of electronic dispute resolution and the role of non-litigation institutions in digital consumer protection.